The use of CONOX as a guide to the general anesthesia on laparotomy patients compared with standard clinical care – A pilot study - Brillyan Jehosua Toar; I Putu Pramana Suarjaya; IGAG Utara Hartawan; Tjokorda Gde Agung Senapathi (Indoscholar, 2021)
Background: Avoiding excessive doses of anesthesia was fundamental, mainly to reduce the adverse effect of anesthesia. Electroencephalography (EEG)-based monitors can be used to measure the depth level of anesthesia and guide intraoperative hypnosis drug and opioid administration. This study aims to evaluate the benefit of using CONOX monitor when administering anesthesia drugs in laparotomy procedures. Method: Twenty patients aged 18-65 years with physical status ASA I-III who underwent major laparotomy surgery with general anesthesia total intravenous anesthesia (TIVA) were divided into two groups. Group A received general anesthesia guided with the CONOX monitor, while group B using standard clinical care. We later evaluate the total use of propofol and fentanyl, intraoperative hemodynamic profile, postoperative cognitive disorder (POCD), intraoperative awareness, postoperative nausea and vomiting (PONV), and moderate to severe pain in the post-anesthesia care unit (PACU). Results: The mean total propofol used is lower in CONOX group (63.6 ± 11.7 mcg/kg/min vs. 74 ± 17.87 mcg/kg/min). A similar result was obtained with fentanyl. The CONOX group use a lower total of fentanyl (212.5 ± 32.3 mcg vs. 249 ± 54.6 mcg) than the control group. POCD was found to be more prevalent in the control group (5 vs 2 patients). While there is no report of intraoperative awareness. Conclusion: The incidence of PONV and moderate to severe pain in PACU was similar between the two groups. This pilot study is a preliminary study to evaluate the benefit of using EEG-based monitors to adjust anesthesia drugs.